2012
DOI: 10.1007/s00120-012-2806-9
|View full text |Cite
|
Sign up to set email alerts
|

Kontroverse Unterkelchstein

Abstract: For many years, the treatment options of lower pole stones have been discussed controversially: Watchful waiting, shock wave lithotripsy, flexible ureterorenoscopy and percutaneous litholapaxy. Small lower pole stones <1 cm can be monitored actively. Shock waves can disintegrate the stones and are recommended for stones <1 cm. However, the stone-free rate is limited because of the particular anatomy of the lower pole. Modern flexible ureterorenoscopes can nowadays reach even anatomically unfavourable lower cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[ 9 ] Other studies have shown that a shorter infundibular length (<22 mm) as well as larger stone size (>10 mm) and burden can decrease stone free rates. [ 3 4 5 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] Other studies have shown that a shorter infundibular length (<22 mm) as well as larger stone size (>10 mm) and burden can decrease stone free rates. [ 3 4 5 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that treatment of lower pole stones (LP) stones has a lower stone free rate (SFR) than other renal or ureteral stones due to the LP anatomy. [ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%